(untitled) (KYAMC Journal, 2013)
Lofgren’s syndrome is an acute form of sarcoidosis that is characterized by erythema nodosum (EN), bilateral hilar lymphadenopathy (BHL) accompanied by arthritis or arthralgia. We are reporting a 32 year old male with Lofgren’s syndrome and then the literature is reviewed. Keywords: lofgren’s syndrome, sarcoidosis. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13520 KYAMC Journal Vol.2(1) 2011 pp.145-148